Casa dos Contos: landscape and memory in Ouro Preto - Keller Costa, Raíssa (2022)
This study presents Casa dos Contos and the city of Ouro Preto from the notion of landscape. The relationships between monument and monument city lead to different readings that reflect their dynamics. The purpose is to present these relationships between the House and the city, retrieving aspects of its history since its construction in the 18th century, as the residence of João Rodrigues de Macedo, until today, as the Casa dos Contos Museum. In the 20th century, the consolidation of the city as a heritage site brought challenges for its preservation, a territory of constant transformation. We used bibliographic research directed towards the notion of landscape and documentary research to understand the history and dynamics of the surroundings of Casa dos Contos in different periods. We hope to contribute to a more sensitive look at the landscape, understanding it as a reflection of subjectivity and of the relationships that one has with space over time.